(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Widyaningrum T, Febrianti N, Prastowo I, Saifuddin MF, Permadi A. 2022. Exploration, screening and identification of indigenous yeast from some palm juices for bioethanol production. Biodiversitas 23: 3984-3990. The major energy sources usually employed are originated mainly from fossil which can run out. Therefore, the creation of ecologically beneficial and long-lasting forms of alternative energy sources, such as bioethanol, is an absolutely necessary. This study aimed to explore, screen and to identify indigenous yeasts from some palm juices for bioethanol production. The isolates were screened in coconut water media for the degree of bioethanol production, the content of reducing sugar based on a DNS method, and the cell number based on optical density (600 nm). Furthermore, identification was performed using ITS and candidates of the highest bioethanol-producing ability including A3A, A11E from Arenga pinnata, K1C1, K1A, K2C from Cocos nucifera L., N3E, N3D, N1A from Nypa fruticans, S1A, and S2D from B. flabellifer L were obtained. The respective bioethanol contents were 13.4%, 12.8%, 13%, 16%, 14.2%, 13.2%, 12%, 12.6%, 14.4%, and 13.35%. The results showed that the isolates of A3A and N3E were similar to those of Pichia deserticola CBS 7119T. Meanwhile, the isolates of K1A and S1A were similar to that of Pichia manshurica CBS 240T and Candida tropicalis ZA 021T.